Modifying SWAT with an energy balance module to simulate snowmelt for maritime regions. (July 2017) - Qi, Junyu; Li, Sheng; Jamieson, Rob; Hebb, Dale; Xing, Zisheng; Meng, Fan-Rui
Abstract: Rain-on-snow events are typical in maritime climates, and they can cause serious floods and excessive losses of soils and nutrients. It is assumed that energy balance snowmelt models (EBMs) perform better in simulating these events than temperature index models (TIMs), due to their consideration of physical conditions. In this study, an energy balance snowmelt model was modified and integrated with the Soil and Water Assessment Tool (SWAT) to predict snowmelt for maritime regions. The modified EBM was tested against field measurements and simulations of the currently used TIM in SWAT for eight watersheds across Atlantic Canada. Results indicated that the EBM improved the accuracy of predicting snowmelt compared with the TIM, especially for watersheds with low forest cover, mainly due to improved simulations of rain-on-snow events. In addition, the EBM was able to provide reliable estimates of snow depths important for simulating soil temperatures during winter in Atlantic Canada. Highlights: SWAT2009 source code is modified to integrate an energy balance snowmelt module. The new module is tested in eight watersheds at an Atlantic maritime region. Modeling of rain-on-snow events is improved by the new module. The new module performs better than the original module in ungauged conditions. The modified SWAT is a better option for application in maritime regions.